2018
DOI: 10.17306/j.afs.2018.0596
|View full text |Cite
|
Sign up to set email alerts
|

Changes in contents of phenolic compounds (sinapic acid derivatives) in seeds of Brassica napus L.under adverse storage conditions [pdf]

Abstract: Background. The quality of rapeseed oil depends to a considerable degree on raw material quality. Negligence in maintaining the appropriate conditions during long-term rapeseed storage (excessively high humidity and temperature) may contribute to a deterioration of seed quality, as a result of microbial growth and changes in native antioxidant contents. The aim of this study was to investigate the effect of inappropriate storage conditions on changes in sinapic acid derivative content, which is the main phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Brassica seeds are rich in bioactive compounds that exhibit antioxidant action and can play a vital role in reducing blood cholesterol levels ( Ratnayake and Daun, 2004 ). In B. napus seeds, the concentrations of phytosterols can be twice that of sunflower and soybean oils ( Vlahakis and Hazebroek, 2000 ), and the content of phenolic compounds can be 10-fold greater than in seeds of other crops ( Siger et al, 2018 ). The abundance of such important biologically active compounds is sensitive to storage conditions.…”
Section: Physiological Impact Of Heat Stress At Different Development...mentioning
confidence: 99%
See 2 more Smart Citations
“…Brassica seeds are rich in bioactive compounds that exhibit antioxidant action and can play a vital role in reducing blood cholesterol levels ( Ratnayake and Daun, 2004 ). In B. napus seeds, the concentrations of phytosterols can be twice that of sunflower and soybean oils ( Vlahakis and Hazebroek, 2000 ), and the content of phenolic compounds can be 10-fold greater than in seeds of other crops ( Siger et al, 2018 ). The abundance of such important biologically active compounds is sensitive to storage conditions.…”
Section: Physiological Impact Of Heat Stress At Different Development...mentioning
confidence: 99%
“…As a result, the degradation of such compounds not only alters the quality of oil but can also lead to the formation of oxidized derivatives with cytotoxic properties ( Rudzińska et al, 2009 ). To investigate the effect of inappropriate storage conditions (13.5% moisture content and 25°C temperature) on seed quality in B. napus , Siger et al (2018) reported an intense growth of fungi along with a decrease in sinapic acid derivatives, the main phenolic compounds in B. napus ( Siger et al, 2018 ). The development of fungal growth not only reduces the time of safe storage but also causes a risk of seed deterioration and mycotoxin contamination posing a serious threat to human and animal health ( Siger et al, 2018 ).…”
Section: Physiological Impact Of Heat Stress At Different Development...mentioning
confidence: 99%
See 1 more Smart Citation